Crystallization and preliminary X-ray crystallographic analysis of the probable tRNA-modification GTPase (TrmE) from Staphylococcus aureus - Priyadarshi, Amit (International Union of Crystallography, 2008)

(untitled)
Probable tRNA-modification GTPase (TrmE) is a guanine nucleotide-binding protein that is conserved between bacteria and humans. GTPase hydrolyzes GTP and plays a pivotal role in signalling pathways. In this study, TrmE from Staphylococcus aureus was overexpressed in Escherichia coli. The enzyme was found to crystallize at 295 K when ammonium sulfate was used as a precipitant. X-ray diffraction data were collected to 2.9 Å resolution from the crystallized enzyme using synchrotron radiation. The crystal was found to belong to the cubic space group I23, with unit-cell parameters a = b = c = 229.47 Å, α = β = γ = 90°. The crystal is likely to contain four monomers in the asymmetric unit, with a corresponding V (M) of 2.4 Å(3) Da(−1) and a solvent content of 50%.